The Use of a Theory of Change Model to Guide the Implementation of a Comprehensive Surgical Specialty Training Program in Equatorial Guinea - Robert Memba; Juan Carlos Puyana; Martha Grayling; Carme Climent; Patrícia Martínez; Eunice Blanco; Jordi Rigueiro; David Suárez; Guillem Viscasillas; Emma Fortea; Olga Roman; Daniel Gracia; et al. (Ubiquity Press, 2024)
Background: Equatorial Guinea (EG) is located on the African west coast, with only 0.4 trained physicians per 1,000 resident population. The country has one medical school and there is no specialist training program. From 2000 to 2022, 524 doctors have received their medical degree. However, the number of national surgical specialists in the entire country is currently 42. Objective: Formación Especializada Sanitaria en Guinea Ecuatorial (FES Guinea) is a program specifically aimed at designing and implementing a long-term national surgical specialist training program. Methods: Más Que Salud (+QS), which means "More than Health" in Spanish, is a nonprofit organization leading the FES Guinea program. We used the theory of change (ToC) framework to evaluate the work accomplished and implement subsequent phases. The initial phase (A) included a needs assessment and mapping of available resources. An intermediate phase (B) started with a memorandum of understanding to implement a Train the Trainer program. The consolidation phase (C) consists of educational interventions and future advanced training projects. Findings: The ToC model allowed us an analyses of initial and intermediate phases. The needs assessments and resources mapping were executed while several scientific meetings and workshops were given. Scholarships to support specialist training abroad benefited six physicians in a diverse set of surgical disciplines. A regulatory commission to implement the FES Guinea program and the National Medical Council of EG were created. Working directly with the EG Ministry of Health, +QS codesigned a National Health Development Plan that began implementation in 2021 to continue until 2025. Conclusions: The ToC model allowed us to predict the current and future potential effects of FES Guinea on surgical workforce development in EG. This is a unique surgical training program, which combined effective initiatives spearheaded initially by an NGO that successfully incorporated both local health and academic authorities, ensuring sustainability.